Effect of swirl generators with different sized propeller on heat transfer enhancement - Cakmak, Gulsah; Argunhan, Zeki; Yildiz, Cengiz (Sila Science, 2011)
In this study, the swirl flow that is one of the passive methods is used for increasing the heat transfer coefficient in the concentric heat exchangers. For this purpose, propeller type swirl generators were prepared to test in the experiments. So, the effect of propellers placed in the inner pipe of the concentric heat exchangers on the heat transfer and pressure drop was investigated experimentally. Experiments were undertaken for the Reynolds Number range of 4000-12000 and for both parallel and counter-flow. It is shown that, the propellers rotated freely with the effect of fluid flowed in the inner pipe are swirling flow generator and they have improved heat transfer. In addition that up to 50% enhancements could be accomplished in heat transfer rates with the swirl generators compared to without the swirl generators. In the parallel flow mode, the enhancement was 10 % lower than that of counter-flow at the same Reynolds number. On the other hand the pressure losses increase approximately 3 times more than the empty tube related to Reynolds numbers and propeller sizes. As an outcome of the study, the results showed that a rather smaller size but the same capacity heat exchanger could be proposed by using these elements imposing swirling to the fluid flowing through inner pipe.
Keywords: Heat exchangers; Turbulators; Pressure drops; Propeller